Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Ecoprint Sebagai Upaya Peningkatan UMKM di Desa Pematang Sijonam Oleh Mahasiswa/I KKN UINSU 2025 - Nazwa Amelia Rangkuti; Neha Chintya; Nur Amira Syafiqah; Nadilla Khairunissa; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2025)
This community service initiative was designed to empower housewives in Dusun III, Desa Pematang Sijonam, by introducing ecoprint as a sustainable craft and a potential driver of micro, small, and medium enterprises (MSMEs). The activity was motivated by the limited access to alternative livelihoods in rural communities and the increasing relevance of environmentally conscious products in contemporary markets. The program adopted a descriptive qualitative design, emphasizing participatory involvement through workshops and direct practice. Participants were guided to identify tannin-rich leaves from their local environment, arrange them on pre-mordanted cotton tote bags, and apply steaming processes to transfer pigments. The outcomes revealed that participants not only acquired technical competence but also demonstrated heightened creativity and confidence, producing distinctive motifs that carried cultural and ecological values. More importantly, the training raised awareness of the economic potential of natural resources that had previously been overlooked. This activity suggests that ecoprint is not merely an artistic expression but also a practical strategy for fostering women’s economic independence, stimulating rural entrepreneurship, and strengthening sustainable development at the community level